Hemostatic imbalance underlying preterm delivery in COVID-19 convalescent patients - M. G. Nikolaeva; A. V. Korchagina; A. P. Momot; E. V. Grigoreva (Акушерство, гинекология и репродукция, 2024)
Aim: to study the role of the hemostatic system in pretem delivery in pregnant women who have had COVID-19 in the gestation period from 14 to 16 weeks.Materials and Methods. A prospective single-center observational study was conducted by enrolling 63 pregnant women with verified COVID-19 at 14–16 weeks of gestation. The main group consisted of 37 patients with preterm birth (PB), comparison group – 26 patients labour activity that occurred at least at gestational age of 37 weeks. Clinical and anamnestic data and dynamic changes in fibrinogen and D-dimer level, activity of tissue factor (TF), tissue factor pathway inhibitor (TFPI), plasminogen activator inhibitor-1 (PAI-1), tissue plasminogen activator (t-PA), urokinase plasminogen activator (u-PA) were analyzed; thrombin generation assay (TGA) was performed.Results. It was found that severity of COVID-19 infection did not determine the timing of delivery that depended on patient comorbid condition. All PB observations (37 out of 63, 58.7 %) were caused by decompensated placental function manifested by acute obstetrical complications: increasing intrauterine fetal hypoxia (64.9 %) along with intrauterine growth retardation (51.4 %), severe preeclampsia (13.5 %) and premature abruption of the normally located placenta (5.0 %). In both study groups, COVID-19 experienced at 14–16 weeks of pregnancy was associated with coagulation and fibrinolytic imbalances. At the same time, at least 6 weeks post-COVID-19 infection, patients with PB had higher level of the “Peak thrombin” vs. comparison group (3050 vs. 2527 pmol/L; p = 0.0433). Also, patients with term vs. preterm delivery had TF activity decreased significantly: by 47.1% and 28.1%, respectively (p = 0.0546). Patients in preterm delivery group were characterized by fibrinolytic imbalance. At the first time point, suppressed fibrinolysis (PAI-1 level – 18.4 vs. 12.5 ng/ml in the comparison group; p = 0.0209) was concomitant with elevated level of u-PA (1.5 vs. 0.55 ng/ml in comparison group, p = 0.0015), which suggests a potential prolonged immunoinflammatory response in patients with PB. Magnitude of fibrinogen concentration and D-dimer level during post-COVID-19 follow-up study was within the reference values specific to gestational age.Conclusion. A significant increase in coagulation potential was found and verified by elevated activity of tissue factor and potential to thrombin generation in COVID-19 convalescent patients. In the case of preterm delivery, there was an imbalance in fibrinolysis system revealed by decreased blood fibrinolytic activity elevating along with increasing gestational age.